2019
DOI: 10.1155/2019/9250472
|View full text |Cite
|
Sign up to set email alerts
|

Experiment on Improving Bearing Capacity of Pile Foundation in Loess Area by Postgrouting

Abstract: Postgrouting technology is an inevitable trend in the development of bored piles in the loess area. To study the behavior of end resistance, lateral friction, and bearing capacity of postgrouting pile and conventional pile, the mechanism of improving the bearing capacity of postgrouting at the end of pile is analyzed by the static load failure test of pile foundation, combined with the principle of grout-soil interaction and Bingham fluid model. The results show that the grout-soil interaction enhances the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In addition, the connection between the soil masses becomes tighter, and the internal friction angle of the soil becomes larger. Similarly, when using the large-scale triaxial test equipment, due to the existence of the circumferential surrounding rocks, the soil was compacted, so the void ratio was reduced, A high-rise building in Nanning Zhou [37] and the internal friction angle was increased, which resulted in the internal friction angle obtained from the large-scale indoor triaxial apparatus being larger than that obtained from the in situ test.…”
Section: Statistical Analysis Of the Recommended Values Of The Mechan...mentioning
confidence: 99%
“…In addition, the connection between the soil masses becomes tighter, and the internal friction angle of the soil becomes larger. Similarly, when using the large-scale triaxial test equipment, due to the existence of the circumferential surrounding rocks, the soil was compacted, so the void ratio was reduced, A high-rise building in Nanning Zhou [37] and the internal friction angle was increased, which resulted in the internal friction angle obtained from the large-scale indoor triaxial apparatus being larger than that obtained from the in situ test.…”
Section: Statistical Analysis Of the Recommended Values Of The Mechan...mentioning
confidence: 99%
“…Geißler [6] investigated compaction grouting for offshore pile foundations and found that the use of grouting significantly increased the load bearing capacity of the system of pile-grout. Zhou [7] performed experiments on enhancing the bearing capacity of pile foundations in the soil of loess area by post-grouting and found that the utilizing of post-grout considerably increased the pile load-bearing capacity. The use of jet grouting greatly increased the stability of the pile-grout system, according to numerical research [8] on the performance of jet grout piles for braced excavations in soft clay.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique formation and geological conditions, loess soil is characterized by containing a great amount of randomly distributed macropores, strong particle bonding, and acute water sensitivity [1][2][3][4][5]. erefore, it is difficult to model the mechanical behavior of loess soil.…”
Section: Introductionmentioning
confidence: 99%